Nanophotonic Device in Combination with Bacteriophages for Enhancing Detection Sensitivity of Escherichia coli in Simulated Wash Water. (22nd September 2019) - Tilton, Lianna; Das, Gautom; Yang, Xu; Wisuthiphaet, Nicharee; Kennedy, Ian M.; Nitin, Nitin
Abstract: Among various approaches to control and monitor cross-contamination of fresh produce, a biosensor that can rapidly detect the presence of a specific bacterium in wash water or on fresh produce can be effective. This research demonstrates the development of a rapid biosensor based on a combination of a nanophotonic device and the bacteriophage T7 for the detection of Escherichia coli without the need for culturing or nucleic acid extraction. This biosensor platform is based on bacteriophage mediated specific lysis of target bacteria and release of β -galactosidase. The enzyme could be further detected by a nanophotonic device that amplifies the fluorescent signal, therefore allowing better sensitivity. Production of β -galactosidase is induced by isopropyl β -D-1-thiogalactopyranoside (IPTG) and the enzyme is then released by bacteriophage lysis, which is detected by the nanophotonic device using a fluorescent enzyme substrate resorufin β -D-galactopyranoside. Using this approach, the results demonstrated successful detection of 10 CFU mL −1 of E. coli BL21 in simulated spinach wash water within 8 hours. Specificity of the assay was demonstrated with negative controls including Pseudomonas fluorescens and Listeria innocua .